Comparing ESL undergraduates' collaborative writing on wiki and in a face-to-face environment - Ansarimoghaddam, Shokoufeh (2014)
Most ESL tertiary students find creating a coherent and extended piece of writing difficult and challenging. In assisting students to improve their writing, collaboration was found to be an effective strategy. The strength of collaboration is exemplified by wikinomics (coined from wiki and economics) that emphasizes the benefits that can be drawn from collaboration in all aspects of human activities, including education,through collective wisdom. Wiki was initially created for developing webpages collaboratively. The efficiency of wiki as a collaboration device has made it a synonym for collaboration that simplifies collaborative writing through its interactive features. Considering the strengths of wiki for collaborative writing, the present study investigates collaborative writing on wiki and face-to-face through comparing the participants’ perceptions and preferences of collaborative writing on wiki and face-to-face, their interaction patterns on the two modes of collaborative writing, and the quality of their individual and collaborative essays after going through a collaborative writing process on wiki and face-to-face. The study employs a mixed-method research design to integrate qualitative and quantitative data collection and analysis. Participants were an intact class of ESL tertiary students in a Bachelor of Arts English language programme. The quantitative data were collected from a quasi-experiment based on a counter-balanced design where participants were randomly assigned to two experimental groups. Each experimental group was given two treatments of collaborative writing on wiki and face-to-face with different sequences of the two treatments. Data were collected from one pre-experiment and two post-experiment essays, two collaborative essays, and two questionnaires. Participants also wrote down their reflections on the collaboration on paper, and they were interviewed at the end of the experiments. The face-to-face groups were audio- and video- taped for investigation of their interaction patterns, and the wiki discussion records were analyzed for salient points. Participants’ interactions were analyzed through a descriptive analysis model adapted from Kumpulainen and Mutanen (1999).